Patient involvement in the safety of care: an integrative review - Thaynara de Oliveira Silva; Ana Lúcia Queiroz Bezerra; Thatianny Tanferri de Brito Paranaguá; Cristiane Chagas Teixeira (Universidade Federal de Goias, 2016)
The aim of this integrative review was to survey the strategies adopted by health institutions that involve patients in care as a barrier to prevent incidents. A search was conducted in MEDLINE, LILACS, CINAHL and PubMed databases using the descriptors 'patient safety', 'iatrogenic', 'medical error' and 'involvement'. The review included studies in full text published between 2003 and March 2016 in English, Spanish or Portuguese. It was found that the effective communication and the development of patients' autonomy are the most advocated strategies. The level of evidence of studies was limited to four and six. The assessment or description of institutional practices involving patients in their safety emerged as a gap in scientific knowledge. The impact of this review is to demonstrate the need for randomized studies to identify effective interventions, directing health institutions towards change in the organizational culture, focusing on safety and patient-centered care.